2011
DOI: 10.4304/jltr.2.1.104-111
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Critical Thinking Ability of Iranian EFL Learners and Their Resilience Level Facing Unfamiliar Vocabulary Items in Reading

Abstract: Abstract-InResilience Scale, a vocabulary checklist, and a validated battery of four reading tests were given to the subjects. In order to empirically investigate the research hypotheses, the subjects were divided into two groups of high and low critical thinking and resilience groups. The results of the analyses for the collected data through t-test revealed that (a) the levels of critical thinking had significant effect on the scores of the subjects on resilience scale, (b) the levels of critical thinking ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
45
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 12 publications
12
45
1
1
Order By: Relevance
“…According to Waters (2006), applying CT activities in English language classrooms that is an important task of language teachers can improve the learners' level of thinking and at the same time can help them to understand the main meanings of the text. Furthermore, EFL learners who are equipped with the ability to think critically feel more efficacious in learning a foreign language (Pajares, 2002).Therefore, it is essential for language teachers to encourage learners to use their CT abilities by providing them challenging opportunities in which they reflect, grow and learn and try to express their opinions critically which can contribute to their progress in language learning (Kamali &Fahim, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Waters (2006), applying CT activities in English language classrooms that is an important task of language teachers can improve the learners' level of thinking and at the same time can help them to understand the main meanings of the text. Furthermore, EFL learners who are equipped with the ability to think critically feel more efficacious in learning a foreign language (Pajares, 2002).Therefore, it is essential for language teachers to encourage learners to use their CT abilities by providing them challenging opportunities in which they reflect, grow and learn and try to express their opinions critically which can contribute to their progress in language learning (Kamali &Fahim, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study also indicated that CT and autonomy of students were highly correlated. Kamali and Fahim (2011) investigated the relationship between CT ability, resilience, and reading comprehension of texts with unknown vocabulary items. The results of t-test revealed that the levels of CT and the levels of resilience had a significant impact on the subjects' reading ability of texts with unfamiliar vocabulary items.…”
Section: Journal Of Language Teaching and Research 389mentioning
confidence: 99%
“…In another similar study Kamali and Fahim (2011) studied the relationship between resilience, reading comprehension of texts containing unknown vocabulary items and critical thinking skill of Iranian EFL intermediate…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Nasirahmadi (2014) concluded in his study that critical thinking can predict 38% of the learners' success in IELTS reading section. Fahim and Kamali's (2011) research also demonstrated that there is a positive correlation between learners' critical thinking ability and their reading comprehension. Moreover, Miller (1981) showed students' achievement in critical thinking was closely associated with their reading proficiency achievement.…”
Section: International Journal Of Research Studies In Language Learnimentioning
confidence: 86%